Drug- and herb-induced liver injury: A case series from a single center - Muhammed Sait Dağ; Musa Aydınlı; Zeynel Abidin Öztürk; İbrahim Halil Türkbeyler; İrfan Koruk; Muhammet Cemil Savaş; Mehmet Koruk; Abdurrahman Kadayıfçı (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Drug-induced liver injury (DILI) is common worldwide and has a potentially fatal outcome. It accounts for more than half of the cases of acute liver failure in the United States. Herb-induced liver injury (HILI) is a less documented condition but a growing problem. We present here the clinical characteristics and outcome of patients with drug- and herb-induced liver injury from our center. Materials and Methods: In this 4-year retrospective study, 82 patients in whom there was a causal or highly probable relationship between herbal medicine or drug use and liver disease are presented. Results: The mean age of patients was 43.1±14.8 years; sexual distribution was 53 females and 29 males. The major cause of hepatotoxicity was drugs (87.8%), with herbal medicine accounting for 12.2%. The leading causative agents were nonsteroidal anti-inflammatory drugs (NSAIDs) (23.1%), followed by antibiotics (19.5%). The pattern of hepatotoxicity was hepatocellular in 35 patients (42.6%), mixed in 28 (34.1%), and cholestatic in 19 patients (23.1%). Teucrium polium (known popularly as felty germander), which is a traditionally used herbal medicine of the Labiatae family in our region, was the most common cause of herb-induced liver injury and responsible in 7 of 10 herbal hepatotoxic cases. Acute liver failure developed in 3 patients (two patients related with flurbiprofen and diclofenac and one patient due to an isoniazid-rifampicin combination). Conclusion: Antibiotics and NSAIDs were the most common etiologic agents for drug-induced liver injury. Surprisingly, herbs follow these groups of drugs and must be questioned more carefully. Turkish Başlık: İlaç ve bitki ilişkili karaciğer hasarı: Tek merkez vaka serisi Anahtar kelimeler: İlaç, bitkisel preparatlar, toksisite, hepatit Arkaplan/Amaç: İlaca bağlı karaciğer hasarı tüm dünya oldukça yaygındır ve ölümle sonuçlanma potansiyeline sahiptir. Birleşik Devletler’ deki akut karaciğer yetmezliği vakalarının yarısından fazlasından sorumludur. Bitkisel ajanlara bağlı karaciğer hasarı daha az dökümente edilse de giderek büyüyen bir problemdir. Bu yazıda merkezimizin ilaç ve bitkisel ajanlara bağlı karaciğer hasarı oluşan hastaların klinik özelliklerini ve sonuçlarını sunduk. Yöntemler ve Gereçler: Dört yılı içeren bu retrospektif çalışmada, ilaç ya da bitkisel ajan kullanımı ile karaciğer hasarı görülen 82 hasta sunuldu. Bulgular: Hastaların 53’ü kadın ve 29’u erkek olup yaş ortalamaları 43.1±14.8 idi. Hepatotoksisitenin majör sebebi ilaçlar olup (% 87.8), bitkisel ilaçların oranı % 12.2 idi. Başlıca sorumlu ajanlar NSAİİ’lerdi (%23.1) ve bunları antibiyotik kullanımı izliyordu (%19.5). Hepatotoksisite 35 hastada (%42.6) hepatosellüler, 28 hastada (%34.1) mikst ve 19 hastada (%23.1) kolestatik tipteydi. Bölgemizde geleneksel bitkisel ilaç olarak kullanılan Labiatae familyasından Teucrium polium (daha çok germander olarak bilinir), bitki ilişkili karaciğer hasarı vakalarının en sık sebebi olup 10 vakanın 7’ sinden sorumluydu. Üç hastada akut karaciğer yetmezliği gelişti (2 hastada flurbiprofen ve diklofenak’ a ve bir hastada izoniazid-rifampisin kombinasyonuna bağlı). Sonuç: Antibiyotikler ve NSAİİ’lar ilaca bağlı karaciğer hasarının en sık etyolojik sebepleriydi. Beklenmedik şekilde bitkisel ajanlar bu grup ilaçları takip ettiğinden etyolojide daha dikkatli sorgulanmalıdır.